Refining concepts for empirical multimodal research: defining semiotic modes and semiotic resources - Castaldi, Jacopo (Frontiers in Communication, 2024)
The issue of defining key concepts in multimodal research is at the same time ongoing and of pivotal importance. Building on John Bateman’s categorisation of modes, and paying special attention to the concept of materiality within the discussion, the paper provides a clear differentiation between semiotic modes and semiotic resources and discusses the relationship between the two. These will be defined by also looking at how they differ from another key concept in multimodal research, i.e., media, and examples will be provided to illustrate how the newly defined concepts can guide empirical investigations of multimodal texts and their reception. The paper aims to continue the discussions around these key concepts amongst multimodal scholars, so that agreement in the field can eventually be reached.